Marco Uccellini’s Sonata Ottava op. 4: Perspectives in Grouping, Meter and Metrical Dissonance - Solá, Eduardo (Música Hodie, 2015)
Rhythmic and metric perception has changed drastically over time, and it is at least dangerous to over- look its significance for performance. Current methods for analyzing grouping and displacement dissonances, here in combination with a unique approach to the elasticity of rhythmic cells, shed some light on the composi- tional complexity in this specimen from seventeenth-century violin repertoire. The main goal in this study is to promote an expansion in contemporary metric/rhythmic perception with special attention to historical context. It also deals with rhythmic notation, challenging the purpose of modern edition making in relation to the origi- nal musical text. Keywords: Violin; Marco Uccellini; Seventeenth (17th) century; Metrical dissonance; Rule of Down-Bow; Musical notation.